2015
DOI: 10.1007/s11270-015-2665-2
|View full text |Cite
|
Sign up to set email alerts
|

Colour Degradation of Simulated Textile Effluent by Electrolytic Treatment and Ecotoxicological Evaluation

Abstract: Since the last century, humanity has sought ways to minimize the impact of the industrial growth in the environment. The textile industry, as one of the major contributors to water pollution, has been dumping coloured effluents which cause great impact in water bodies. The electrolytic process not only degrades the colour of the effluent but also transforms recalcitrant substances by direct or indirect oxidation. The ecotoxicological tests are used nowadays as a way to verify the toxicity degree of water bodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…After a 2-day examination, the irrigated seed germination decreased with increasing concentration. On the other hand, no toxicity to Acid Blue 40 and Acid Red 151 after 15 minutes of electrolytic treatment was found 61 .…”
Section: Possible Adsorption Mechanismmentioning
confidence: 91%
See 1 more Smart Citation
“…After a 2-day examination, the irrigated seed germination decreased with increasing concentration. On the other hand, no toxicity to Acid Blue 40 and Acid Red 151 after 15 minutes of electrolytic treatment was found 61 .…”
Section: Possible Adsorption Mechanismmentioning
confidence: 91%
“…A similar method was used in our previous work in which we studied the effect of two anionic and two cationic dyes on lettuce and mustard seeds 28 . The results showed that the shooting of germinated seeds (clover, wheat, lettuce, tomato) is dye dependent 61 . After a 2-day examination, the irrigated seed germination decreased with increasing concentration.…”
Section: Possible Adsorption Mechanismmentioning
confidence: 99%
“…The results comparison revealed that the yeast biomass and the cross-linked chitosan beads achieved a decrease in the toxicity of the dye in the solution (Table 5). Despite the lower microcrustacean mortality after dye removal, this reduction was not statistically relevant [20].…”
Section: Toxicity Test With Microcrustacean D Similismentioning
confidence: 84%
“…The number of living organisms was then counted. The tests were performed with four replicates and were submitted to non-parametric statistical analyses using the Kruskal-Wallis method with the aid of the BioEstat 4 program, which is the most suitable analysis for comparative bioassays [20].…”
Section: Ft-ir Spectrophotometrymentioning
confidence: 99%
“…Franco et al (2017) have evaluated the effects of different doses of sanitary landfill leachate on the germination of lettuce seeds and observed a 100 % inhibition of germination with 1.0 mL of the pollutant. In evaluating the efficiency of the electrolytic process in treating effluents from the textile industry through bioassays with seeds of lettuce (Lactuca sativa Linnaeus, 1753), arugula (Eruca sativa Linnaeus, 1753), and cucumber (Cucumis sativus Linnaeus, 1753), Moraes and Bidoia (2015) found that electrolytic treatment was successful and indicated a low toxicity to the organisms tested. According to Souza et al (2005), plant seeds are highly suitable for bioassays, mainly because the germination process begins when the seeds are rehydrated.…”
Section: Introductionmentioning
confidence: 99%